Winsor Phase Diagram of a Colloidal System from the Mixture of Water, Eugenol, and Tween 20 - Afwa Hayuningtyas; Pinyapat Jitphongsaikul; Alwani Hamad (Research in Chemical Engineering, 2022)
One factor that influenced colloidal structure is the composition of water, oil, and surfactant in the emulsions. This study aims to build a Winsor phase diagram of a mixture of water, eugenol, and Tween 20 and understand the physical differences in a range of micellar structures from the different compositions of the combinations. There were eleven samples with varying compositions of water, eugenol, and tween 20, and then were mixed and observed in parameters such as phase, appearance, and consistency. The results showed that the emulsion's compositions ingredients affected the character of the final emulsion. There were three categories of emulsions as described in the Winsor phase diagram. Water in oil (w/o) microemulsion was formed in the higher oil composition. In contrast, the lower oil content was macroemulsion/ coarse emulsion. The balance of oil and water composition was categorized as a bicontinuous microemulsion. This diagram will further help in constructing the suitable emulsion category for specific purposes.